Regulation of Epstein-Barr Virus Latency Type by the Chromatin Boundary Factor CTCF - Chau, Charles M. (American Society for Microbiology, 2006)
Epstein Barr virus (EBV) can establish distinct latency types with different growth-transforming properties. Type I latency and type III latency can be distinguished by the expression of EBNA2, which has been shown to be regulated, in part, by the EBNA1-dependent enhancer activity of the origin of replication (OriP). Here, we report that CTCF, a chromatin boundary factor with well-established enhancer-blocking activity, binds to EBV sequences between the OriP and the RBP-Jκ response elements of the C promoter (Cp) and regulates transcription levels of EBNA2 mRNA. Using DNA affinity, electrophoretic mobility shift assay, DNase I footprinting, and chromatin immunoprecipitation (ChIP), we found that CTCF binds both in vitro and in vivo to the EBV genome between OriP and Cp, with an ∼50-bp footprint at EBV coordinates 10515 to 10560. Deletion of this CTCF binding site in a recombinant EBV bacterial artificial chromosome (BAC) increased EBNA2 transcription by 3.5-fold compared to a wild-type EBV BAC. DNA affinity and ChIP showed more CTCF binding at this site in type I latency cell lines (MutuI and KemI) than in type III latency cell lines (LCL3456 and Raji). CTCF protein and mRNA expression levels were higher in type I than type III cell lines. Short interfering RNA depletion of CTCF in type I MutuI cells stimulated EBNA2 mRNA levels, while overexpression of CTCF in type III Raji cells inhibited EBNA2 mRNA levels. These results indicate that increased CTCF can repress EBNA2 transcription. We also show that c-MYC, as well as EBNA2, can stimulate CTCF mRNA levels, suggesting that CTCF levels may contribute to B-cell differentiation as well as EBV latency type determination.